Pogled na slovensko jezikovno krajino - Snoj, Marko (Slavia Centralis, 2020)
A Glance at the Linguistic Landscape in Slovenia The paper presents an analysis of all public signs as seen in Nazorjeva ulica in the centre of Ljubljana. The sample inspection shows that among 107 linguistic signs of that particular public space, at least 31% are not written in Slovene and are neither foreign company names nor foreign trade marks. The results have been compared with the actual Slovene legislation and the web inquiry Languages in Slovenia and the Slovenian Language abroad (the target research project “Slovenian Language Policy and User Needs”) conducted on this matter in summer 2017.